Revealing the Relationship between Loneliness and Sleep Quality in Migrating Employees - Hartanto, Aurelia Tiffany; Wibowo, Doddy Hendro (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Individuals who work outside the city often feel lonely, which can adversely affect their sleep quality. This study aims to determine the correlation between loneliness and sleep quality in employees who migrate. The hypothesis of this study is that there is a positive relationship between loneliness and sleep quality in overseas employees. In this study using accidental sampling technique. The subjects involved in this study amounted to 100 employees who migrated in Jakarta with an age range of 18-30 years and lived alone in boarding houses or rented houses. The data collection method uses the Sleep Quality Scale (SQS) and the Russell-University of California Los Angeles (R-UCLA) loneliness scale version 3. The data analysis technique used is the Spearman rank correlation coefficient. Based on the results of data analysis, the correlation coefficient was 0.581 and the p value = 0.000 (p<0.05). These results indicate that there is a significant positive relationship between loneliness and sleep quality, meaning that the higher the loneliness felt by overseas employees, the higher the poor sleep quality. Thus, reducing loneliness will improve sleep quality in overseas employees.Individu yang bekerja di luar kota seringkali merasakan kesepian yang dapat berdampak buruk bagi kualitas tidurnya. Penelitian ini bertujuan untuk mengetahui hubungan antara kesepian dengan kualitas tidur pada karyawan yang merantau. Hipotesis penelitian ini adalah terdapat hubungan positif antara kesepian dengan kualitas tidur pada karyawan rantau. Dalam penelitian ini menggunakan teknik accidental sampling. Subjek yang terlibat dalam penelitian ini berjumlah 100 karyawan yang merantau di Jakarta dengan rentang usia 18-30 tahun dan tinggal sendirian di kos atau kontrakan. Metode pengumpulan data menggunakan skala Sleep Quality Scale (SQS) dan skala Russel-University of California Los Angeles (R-UCLA) loneliness scale versi 3. Teknik analisis data yang digunakan adalah Spearman rank correlation coefficient. Berdasarkan hasil analisis data, didapatkan koefisien korelasi sebesar 0,581 dan nilai p = 0,000 (p<0,05). Hasil tersebut menunjukkan bahwa terdapat hubungan positif signifikan antara kesepian dengan kualitas tidur artinya semakin tinggi kesepian yang dirasakan karyawan rantau maka semakin tinggi kualitas tidur yang buruk. Dengan demikian mengurangi kesepian akan meningkatkan kualitas tidur pada karyawan rantau.